Channels occipital venous sinus in pre-Columbian Peruvian aborigines - Palma, Ricardo (1956)
This brief anatomical research work refers exclusively to occipital bones and skulls of Peruvian natives who lived in the Inca Empire, as well as anatomical peculiarities that once I studied skulls from the same era. This last study I expanded it later, together with my assistants, checking Indians who currently inhabit our territory, the existence of pontine pit, the pit Aymara and other peculiarities in the bodies used in anatomical dissection and autopsy practiced in hospitals.